2D ultrasonic reflection tomography by linear array transducer and wave reflector - Sanpanich, A.; Hamamoto, K.; Sangworasil, M.; Pintavirooj, C. (My University, 2009)
In general, it was known that when the series of an ultrasonic broadband pulse travel through living organ or soft tissue, their reflected projection data can be used to reconstruct a novel tomographic image. Whereas, a data obtain from an ultrasonic tomography in transmission mode is not able to be used for reconstruction a characteristic image of soft tissue which naturally shadowed by a bone or hard tissue. An ultrasonic tomography in reflection mode is realized to be a solution for this problem. However the implementation to identify the projection by using an integrated attenuation coefficient of tissue from the pulsed wave ray path in reflection mode is still more complicated. In this paper, we propose a simulation in 2D of a reflection-mode ultrasonic tomographic system by using the linear array transducer and also a frequency centroid shift method to calculate the projection data. The imaging setup system was enhanced by wave reflecting plate in order to increase an echo wave path. The ultrasound wave paths of our simulation system were intend to focus on the fan beam trajectory which is rather close to a real propagation of the ultrasound wave traveling through soft tissue and ART was used finally as an image reconstruction algorithm. The obtained output shows that our system is more practical and possible toward for using in a clinical trial.
Keywords: ART reconstruction; Ultrasound reflection tomography; Wave reflector